2018
DOI: 10.1108/rpj-12-2016-0207
|View full text |Cite
|
Sign up to set email alerts
|

Post-processing of FDM parts to improve surface and thermal properties

Abstract: PurposeThe purpose of this paper is to develop a novel post-processing technique of fused deposition modeling (FDM) parts to improve surface roughness and reduce heat absorption and for high-temperature application in thermoforming process. Design/methodology/approachThe current technique consists of chemical treatment, drying and aluminum coating. First, surface morphology was investigated using FDM specimens with a flat surface. The heat absorption characteristic was also analyzed by Taguchi-based design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Other approaches for enhancing the mechanical properties of printed components include reinforcing polymers with fillers such as montmorillonite [57], with discontinuous fibers [9,10] and with continuous fibers [58,59,60,61]. Additionally, some researchers have used post-processing techniques to enhance surface quality, strength and tightness [62,63]. Nevertheless, the characterization of parts printed with reinforced polymers and post-processing are beyond the scope of this review paper.…”
Section: Experimental Characterization Of Mechanical Propertiesmentioning
confidence: 99%
“…Other approaches for enhancing the mechanical properties of printed components include reinforcing polymers with fillers such as montmorillonite [57], with discontinuous fibers [9,10] and with continuous fibers [58,59,60,61]. Additionally, some researchers have used post-processing techniques to enhance surface quality, strength and tightness [62,63]. Nevertheless, the characterization of parts printed with reinforced polymers and post-processing are beyond the scope of this review paper.…”
Section: Experimental Characterization Of Mechanical Propertiesmentioning
confidence: 99%
“…Some works combine vapor smoothing with other finishing techniques. For instance, Nguyen et al [ 23 ] carried out a design-of-experiments-based investigation on the treatment of ABS parts combining an acetone-based chemical treatment, drying, and aluminum coating, observing a decrease in surface roughness and heat absorption of radiative heating. Maciag et al [ 24 ] performed a study on the influence of acetone smoothing and subsequent galvanic copper plating over the surface parameters of ABS prints.…”
Section: Introductionmentioning
confidence: 99%
“…Abrasive milling was combined with FDM in Tomal et al (2018) to enhance surface roughness. Chemical treatment and coating were used in Nguyen and Lee (2018) to improve surface roughness. In the review paper (Kumbhar and Mulay, 2018), it was concluded that laser micro machining can be adopted to improve roughness.…”
Section: Introductionmentioning
confidence: 99%